Дистанционная нейтронная терапия в Томске: 40 лет на службе онкологии; Сибирский онкологический журнал; Т. 23, № 1 - Старцева Жанна Александровна Ж. А.; Грибова Ольга Вячеславовна О. В.; Великая Виктория Валерьевна В. В.; Сухих Е. С. Евгения Сергеевна; Лисин Валерий Андреевич В. А.; Новиков Валерий Александрович В. А. (2024, 2024)
Заглавие с экрана